NCAPD3 promotes diffuse large B-cell lymphoma progression through modulating SIRT1 expression in an H3K9 monomethylation-dependent manner - Tiange Lu; Juan Yang; Yiqing Cai; Mengfei Ding; Zhuoya Yu; Xiaosheng Fang; Xiangxiang Zhou; Xin Wang (Journal of Advanced Research)
Introduction: Condensin, a family of structural maintenance of chromosome complexes, has been shown to regulate chromosome compaction and segregation during mitosis. NCAPD3, a HEAT-repeat subunit of condensin II, plays a dominant role in condensin-mediated chromosome dynamics but remains unexplored in lymphoma. Objectives: The study aims to unravel the molecular function and mechanism of NCAPD3 in diffuse large B-cell lymphoma (DLBCL). Methods: The expression and clinical significance of NCAPD3 were assessed in public database and clinical specimens. Chromosome spreads, co-immunoprecipitation (co-IP), mass spectrometry (MS), and chromatin immunoprecipitation (ChIP) assays were conducted to untangle the role and mechanism of NCAPD3 in DLBCL. Results: NCAPD3 was highly expressed in DLBCL, correlated with poor prognosis. NCAPD3 deficiency impeded cell proliferation, induced apoptosis and increased the chemosensitivity. Instead, NCAPD3 overexpression facilitated cell proliferation. In vivo experiments further indicated targeting NCAPD3 suppressed tumor growth. Noteworthily, NCAPD3 deficiency disturbed the mitosis, triggering the formation of aneuploids. To reveal the function of NCAPD3 in DLBCL, chromosome spreads were conducted, presenting that chromosomes became compact upon NCAPD3 overexpression, instead, loose, twisted and lacking axial rigidity upon NCAPD3 absence. Meanwhile, the classical transcription-activated marker, H3K4 trimethylation, was found globally upregulated after NCAPD3 knockout, suggesting that NCAPD3 might participate in chromatin remodeling and transcription regulation. MS revealed NCAPD3 could interact with transcription factor, TFII I. Further co-IP and ChIP assays verified NCAPD3 could be anchored at the promoter of SIRT1 by TFII I and then supported the transcription of SIRT1 via recognizing H3K9 monomethylation (H3K9me1) on SIRT1 promoter. Function reversion assay verified the oncogenic role of NCAPD3 in DLBCL was partially mediated by SIRT1. Conclusion: This study demonstrated that dysregulation of NCAPD3 could disturb chromosome compaction and segregation and regulate the transcription activity of SIRT1 in an H3K9me1-dependent manner, which provided novel insights into targeted strategy for DLBCL.